Systematic Literature Review: Permasalahan Ransomware pada Aplikasi Berbasis Cloud - Zidnii Ilma Rimbarawa; Elis Kholisoh; Zahwa Putri Rahmayani (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2021)
Ransomware has created questions on the security aspects of a cloud architcture, especially with cloud services being adopted by more enterprises. Ransomware encrypts data and makes it inaccessible. Victims are given instructions to pay the attacker a fee in exchange for having their data accessible again. Ransomware has organizations and is increasingly targeting applications running on databases. To prevent this problem, this study uses the Systematic Literature Review method to provide information about ransomware problems in cloud-based applications, as well as ransomware prevention in cloud-based applications and its challenges including the differences in effectiveness for each type of ransomware and the strategies that do not apply to server-side attacks. The research review shows that backup and recovery is a key defense strategy against ransomware. Ransomware protection, applications, and databases require the right strategy, including reliable recovery. This research is useful to ensure that the cloud-based is protected from ransomware attacks.